1980
DOI: 10.1104/pp.66.1.182
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Incorporation of Selenomethionine into Protein by Vigna radiata Polysomes

Abstract: Vigna radiata polysomes efficiently incorporated 175Selselenomethio-nine, I"4Clmethionine, and I'4Clleucine in vitro. The optimal conditions for translation were determined to be 4.8 millimolar Mg2e, 182 milHimolar K+, and pH 7.4. The rates of incorporation of 175Selselenomethionine and 1'4CImethionine were similar when measured separately, but 175Selseleno-miethionine incorporation was 35% less than 14Clmethionine incorporation when both amino acids were present in equal molar concentrations. Polyacrylamide g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…There is a great difference in the plant uptake, transformation and distribution of Se (VI) and Se (IV), and Se (VI) and Se (IV) absorption and transport mechanism are relatively independent. Eustice et al (1980) found that selenate was more easily transported than selenite and the organic Se selenomethionine (SMT), Terry et al (2000) demonstrated the same conclusion. When selenate was absorbed, the ratio of plant Se concentration and root Se concentration was 1.4-1.72, while the ratio range was 0.6-1 when they absorbed selenomethionine (SMT); the ratio range was <0.5 when they absorbed selenite (Zayed et al, 1998).…”
Section: Discussionmentioning
confidence: 72%
“…There is a great difference in the plant uptake, transformation and distribution of Se (VI) and Se (IV), and Se (VI) and Se (IV) absorption and transport mechanism are relatively independent. Eustice et al (1980) found that selenate was more easily transported than selenite and the organic Se selenomethionine (SMT), Terry et al (2000) demonstrated the same conclusion. When selenate was absorbed, the ratio of plant Se concentration and root Se concentration was 1.4-1.72, while the ratio range was 0.6-1 when they absorbed selenomethionine (SMT); the ratio range was <0.5 when they absorbed selenite (Zayed et al, 1998).…”
Section: Discussionmentioning
confidence: 72%
“…A few comparable in vitro plant studies have focused on the following three aspects of selenium biochemistry: (a) aminoacylation of tRNA with selenoamino acids (2,3,21,24); (b) interactions of selenomethionine with methionine adenosyltransferase (12); and (c) the translational incorporation of selenomethionine into protein (5). Yet, in none of these studies in which selenium-sensitive plants were used, was a biochemical reaction correlated with selenium toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…One of these analogs, selenomethionine, is known to be formed by a wide variety of plants (7,9,(16)(17)(18). Although the biochemical characteristics of selenomethionine resemble those of methionine in a great many ways, the metabolic activity of selenomethionine apparently differs in certain respects; one of these differences is, in general, reaction rate (4,5,11,12). Examination of those reactions in which selenomethionine functions at a rate different than methionine could reveal some of the factors that underlie selenium toxicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of wheat germ postribosomal supernatant solutions (S-150) and methods for the translation assays were carried out as described previously (1).…”
mentioning
confidence: 99%